Human trafficking from a human rights perspective: prevention, combat, protection victims and international cooperation (Revista do Tribunal Regional Federal da 3ª Região, 2019)
How to understand the traffi cking in persons in the contemporary order? What are the international and regional standards? What measures should be taken to prevent and eradicate traffi cking in persons and to protect the rights of traffi cked persons? What are the main challenges and prospects? These are the central issues to inspire this study, whose objective is to focus on the issue of traffi cking in persons with a human rights approach, highlighting global, regional and national policies.
Keywords: trafficking in persons; international human rights law; UN system; interamerican system